Surface roughness of enamel and root surface after scaling, root planning and polishing procedures: An in-vitro study - Yildirim, Tuba Talo; Oztekin, Faruk; Keklik, Esra; Tozum, Melek Didem (Elsevier B.V., 2021)
Objectives: The aim of this study was to evaluate enamel and root surface roughness on exracted human teeth by using different tecniques (ultrasonic scaler, hand instruments, polishing paste, pumice and air powder system). Materials and methods: A total of 200 samples were divided into two groups (enamel and root) randomly with 100 samples for each enamel and root groups. The groups were divided into 5 subgroups: Group I: ultrasonic scaler, group II: hand instruments, group III: polishing paste, group IV: pumice, group V: air-powder. Surface roughness (Ra) was assessed with Mitutoyo SJ-410 device. The one-way analysis of variance (ANOVA) test along with the Tukey test was used for statistical analysis. P values less than 0.05 were considered statistically significant. Results: The use of ultrasonic scalers caused the highest roughness increase on the enamel surface (0.935 ?± ?0.010), whereas the use of pumice was the least (0.896 ?± ?0.018) (p ?< ?0.05). There was a significant difference between ultrasonic scalers and all the groups (hand instruments, polishing paste, pumice and air powder system) on enamel surface (p ?< ?0.05). Maximum surface roughness increase was observed in the ultrasonic scalers on root surface. There was a significant difference between ultrasonic scalers and polishing paste, pumice and air powder on root surface, respectively (p ?< ?0.05). Conclusion: The use of ultrasonic scalers cause more rough enamel and root surfaces than hand instrumentation and polishing tecniques. Clinical relevance: Uneven surfaces adversely affect the intended periodontal healing by creating a retention area of microbial dental plaque. © 2021
Keywords: Cementum; Dentin; Enamel; Root; Roughness; Surface